Growth Differentiation Factor-15 in Immunity and Aging - Pence, Brandt D. (Frontiers in Aging, 2022)
Aging increases susceptibility to and severity of a variety of chronic and infectious diseases. Underlying this is dysfunction of the immune system, including chronic increases in low-grade inflammation (inflammaging) and age-related immunosuppression (immunosenescence). Growth differentiation factor-15 (GDF-15) is a stress-, infection-, and inflammation-induced cytokine which is increased in aging and suppresses immune responses. This mini review briefly covers existing knowledge on the immunoregulatory and anti-inflammatory roles of GDF-15, as well as its potential importance in aging and immune function.